HEALTH-RELATED QUALITY OF LIFE (HRQoL) OF ACADEMICIANS IN PUBLIC UNIVERSITIES, MALAYSIA - Nur Zainie Abd Hamid; Shamsinar Ibrahim; Hasyimah Razali; Kamarul Ariffin Mansor, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This empirical paper presents findings from a study concerning the Health-Related Quality of Life (HRQoL) of academicians in Malaysian publicly-funded universities. The main objective of the study was to compare the Health-Related Quality of Life (HRQoL) of the academicians in the selected public universities with the key indicators of the overall and the eight health domains of general Malaysian population norms. A structured e-mail survey was created that includes a link to the validated Short Form 36 (SF-36) items. An e-mail was sent to all respondents of nine randomly selected public universities using registered organisational e-mail to collect the data. Descriptive analysis was used to analyse the data. The percentage of responses was 34.55% and 1235 data were deemed to be usable. The ratio of men to women was 1:1.42. The overall mean score of the Health-Related Quality of Life (HRQoL) in the study was juxtaposed with the overall mean score of the recommended Malaysian general population norms of 65.0. The accumulated score was 50.60, which is lower than the recommended value. All mean scores of the eight-health domain were also lower than recommended mean scores of the general Malaysian population for each health domain. Moreover, gender analysis indicated that male academicians had higher Health-Related Quality of Life (HRQoL) for all the health domains except for Role-Physical (RP) and Social Functioning (SF). Given the lower Health-Related Quality of Life (HRQoL) among academicians than the general population, fair attention should be given by the government and policy-makers to the state of their health, physically and mentally, to ensure continuous improvements in education.